Monitoring of Hematological Indices in Prediction of Outcomes in Critical Conditions in Neuroreresistance Patients - Eshonov Olim Shoyimkulovich; Boltayev Elmurod Bekmurod ugli (Genius Journals, 2023)
The objects of the study were 50 patients with acute cerebral insufficiency (a complication of ischemic and hemorrhagic stroke, as well as traumatic brain injury) aged 32 to 65 years (mean age was 56,3 ± 3 years), in whom clinical (systemic indicators) were analyzed. hemodynamics and respiration, neurological status), instrumental (ECG, chest X-ray, MSCT examination of the brain) and laboratory data (leukoformula, IRNL). Comparison of clinical and laboratory parameters was carried out in three stages: the first stage - on admission, the second stage - the 3rd day, the third stage - the 7th day of intensive therapy. It has been established that a high rate of IRNL is a reliable indicator of the clinical deterioration of the condition of patients and a predictor of an unfavorable outcome of critical conditions caused by acute cerebral insufficiency
Keywords: ischemic and hemorrhagic stroke; craniocerebral injury